Pengaruh Kompensasi Terhadap Turnover Melalui Kepuasan Kerja Barista pada Coffeeshop Didaerah Hollywood Boulevard Cikarang Utara - Dikha Septiani Dewi; Enjang Suherman; Laras Ratu Khalida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of compensation on level turnover by considering their level of job satisfaction in several ways, such as coffee shops around Hollywood Boulevard and North Cikarang. The research methodology used is a quantitative descriptive approach using a Likert scale and questionnaires to collect data. The population of this study consisted of all baristas who worked at Hollywood Boulevard Cikarang Utara. Sampling was carried out using the saturated sampling technique. The results of the analysis using SmartPls version 3.2.9 showed that job satisfaction (M) has a negative effect of -0.256 on turnover (Y) and is significant with a t value of 2.517 greater than 1.96, Compensation (X) has a positive impact of 0.394 on job satisfaction (M) and is substantial with a t value of 3.505 greater than 1.96, Compensation (X) has an effect negative of -0.470 against turnover (Y) and significant with a t value of 5.752 greater than 1.96, compensation (X) for turnover (Y) through job satisfaction (M) has a positive effect of -0.101 and is significant with a t value of 2.254 which is greater than 1.96.